A2_5 The Use of the Bittorrent Protocol in Space Networks - Meredith, Calum James; Boulderstone, David; Clapton, Simon (Physics Special Topics, 2011)
The applications and benefits of the use of a peer-to-peer networking protocol, such as the Bittorrent protocol, are investigated. It is found that an Earth-Mars distributed network can be entirely updated within 35.6 minutes.